Perbandingan Keberhasilan Pemasangan Laryngeal Mask Airway (LMA) ProSeal antara Tehnik Head Extension dan Tehnik Digital Standard - , dr. Ratih Kumala Fajar Apsari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Introduction : Head extension maneuvers in opening airway is well understood in anesthesia field and emergency case , but the effect of insertion LMA Proseal is not understood. Insertion of the LMA requires deep anesthesia to suppress airway reflexes. Modification of the technique is mostly done to improve the success of LMA insertion. The purpose of study is to evaluate the hypothesis that the first attempt success rate of LMA Proseal insertion is higher in Head Extension methode compared to Digital Standard methode. Method : A prospective, Randomized Controlled Trial parallel design study in 86 healthy patients ,male and female patients of 18-50 years old, ASA I or II undergoing general anesthesia. Subjects are patients undergoing elective surgery with general anesthesia in Dr Sardjito Hospital Yogyakarta. Patient were randomly allocated into one of two groups to recieve Head Extension methode , group n=43 and Digital Standard methods, groups n=43. Result : Ease of LMA insertion assessed in this study. The first attempt success rate was compared between the groups. The success of LMA insertion on the first attempt which is considered effective to keep the airway after the first attempt and requires no clinical improvement and position can be properly ventilated and oxygen saturation above 95%.The success of LMA insertion on the first attempt were statistically significant higher in the group Head Extension (95.3%) compared with digital standard group (81.3%) (p <0.05). LMA Proseal insertion speed also significantly different between groups Head Extension (6:51 Â± 2640) seconds compared with a digital standard group (16:44 Â± 5530) seconds. Conclusion : The first attempt success rate of LMA Proseal insertion is higher in head extension methode compared to Digital Standard methode.